Out-of-stock versus sold-out: Consumers' cognitive processes triggered by unavailability marks in online shopping malls - Rhee, Cheul; Park, Wooseok (Asia Pacific Journal of Information Systems, 2020)
In online shopping, "out-of-stock" and "sold-out" are used to indicate product unavailability, and this unavailability and its effects on consumers' behaviors have been studied with great interest for practical purposes. However, few studies have specifically discussed out-of-stock and sold-out products in the same paper. We hypothesized that consumers might cognitively interpret items marked out-of-stock and sold-out differently, and in this paper, we studied these potential differences from the perspectives of consumers' emotions, behaviors, and loyalty based on the stimulus-organism-response framework. In order to explore the differences, we used a multi-method approach that consisted of experiments, surveys, and interviews. Specifically, we built an experimental website on which the same products were categorized as either out-of-stock or sold-out, and we measured the participants' emotions, attitudes, and intentions after the experiment. After two weeks, we conducted interviews to confirm our results and to learn more about consumers' everyday behavior. In the results, males and females demonstrated differences in emotion, behaviors, and loyalty with the interaction effects of an item's being marked out-of-stock versus sold-out. We found that the consumers demonstrated different levels of loyalty based on whether the item was marked out-of-stock or sold-out. We discuss the strategic implications of our findings.
Keywords: Attribution theory; Consumer emotion; Online retailers; Out-of-stock; Sold-out